Occurrence and diversity in host by Mistletoes from fire families in East Melghat Forest - Kokate2, S. P. Rothe1*, G. D. Muratkar2; U. R. (Current Botany, 2011)
The present paper deals with an intensive and extensive exploration of diversification in host by the Mistletoes from fire families like Loranthaceae, Viscaceae from East Melghat Forest. During exploration from 2005-2010, It was noted that Mistletoes as aerial partial parasite found on the number of host plants. On the basis of their occurrence the hosts are categories as principle host, secondary host and Minor host. In all during frequent visits to these forest areas on above said period by the authors, a record of 10 host plants used by the Mistletoes is noticed. This is the first report about the occurrence of Mistletoes on large number of host plants. Paper also includes some of the harmful effects caused by the Mistletoes on the forest vegetation.